Pengaruh Penggunaan Model Pembelajaran Problem Based Learning (PBL) Terhadap Proses dan Hasil Belajar Siswa pada materi Gaya di SMA Negeri 2 Tondano Kelas X - Kalele, Elshadai Christiani; Taunaumang, Heindrich; Rende, Jeane Cornelda (Charm Sains: Jurnal Pendidikan Fisika, 2022)
The use of varied learning models will make the transfer of knowledge more effective and efficient. Problem Based Learning (PBL) learning model is the right learning model. Students are required to solve the problems presented by digging as much information as possible. This study aims to determine the effect of the Problem Based Learning (PBL) learning model on the process and results in learning force material. The type of research used in this research is experimental research. This research was conducted at SMA Negeri 2 Tondano in the odd semester of the 2021/2022 academic year. The subjects in this study were students of class X SMA Negeri 2 Tondano, totaling 21 students. The instrument used for process data is a questionnaire and for student learning outcomes data is a test instrument in the form of description questions. The data analysis technique uses simple linear regression for the process and the results of the coefficient formula show that there is an influence of the Problem Based Learning (PBL) learning model on the student learning process at SMA Negeri 2 Tondano with a percentage results of 51%. Based on the significance value: the Coefficients table obtained a significance value of 0.000 <0.05, so it can be concluded that the variable X (Problem Based Learning model) has an effect on Y (Student Learning Process). .And data analysis techniques for result using the test N-GAIN obtained the average value of the pretest is 17.77 and the average value of the posttest is 74.33. The results of this study indicate that the Problem Based Learning (PBL) learning model has an effect on the process and results.